2021
DOI: 10.1021/acsearthspacechem.1c00292
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Acid (HONO) Formation from the Irradiation of Aqueous Nitrate Solutions in the Presence of Marine Chromophoric Dissolved Organic Matter: Comparison to Other Organic Photosensitizers

Abstract: Nitrous acid (HONO), a highly reactive trace atmospheric gas, is often underestimated in global atmospheric models due to the poor understanding of its sources and sinks, especially in the marine boundary layer (MBL). Herein, we have investigated HONO formation from the irradiation of nitrate solutions in the presence of increasingly complex photosensitizers including marine dissolved organic matter (m-DOM), which contains chromophoric organic matter, collected from a large-scale mesocosm experiment. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 45 publications
3
61
0
Order By: Relevance
“…The fraction of NO3at the surface is larger in the presence of halides in sea salt aerosols (Wingen et al, 2008;Richards-Henderson et al, 2013;Zhang et al, 2020). Other factors that could contribute to higher EFs include high aerosol [H + ] (Scharko Mora Garcia et al, 2021) and the presence of organic species that can act as photosensitizers, H-donors, electron donors, or promote secondary reactions (Ye et al, 2019;Mora Garcia et al, 2021). Laboratory studies on NaNO3 and NH4NO3 particles find EFs of less than 10 (Shi et al, 2021), suggesting that aerosol composition is an important factor in the photolysis rate of pNO3 -.…”
Section: Nox In the Remote Troposphere: Interpreting The Atom Datamentioning
confidence: 99%
“…The fraction of NO3at the surface is larger in the presence of halides in sea salt aerosols (Wingen et al, 2008;Richards-Henderson et al, 2013;Zhang et al, 2020). Other factors that could contribute to higher EFs include high aerosol [H + ] (Scharko Mora Garcia et al, 2021) and the presence of organic species that can act as photosensitizers, H-donors, electron donors, or promote secondary reactions (Ye et al, 2019;Mora Garcia et al, 2021). Laboratory studies on NaNO3 and NH4NO3 particles find EFs of less than 10 (Shi et al, 2021), suggesting that aerosol composition is an important factor in the photolysis rate of pNO3 -.…”
Section: Nox In the Remote Troposphere: Interpreting The Atom Datamentioning
confidence: 99%
“…Both NO 2 and O 2 •− are precursors of HONO and/or NO 2 − reactions (8-11). Besides, another study suggested the aqueous electron reduces nitrate into nitrite reaction (14) (Mora Garcia et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…On a related note, the significance of photosensitization by BrC (via formation of solvated electrons; Wang et al, 2021) and marine dissolved organic matter (via O 2 •formation; Garcia et al, 2021) in enhanced nitrite production from nitrate photolysis have been reported. A recent study from our group has shown that glyoxal photo-oxidation mediated by both nitrate photolysis and photosensitization can significantly enhance the atmospheric sink of glyoxal (Zhang et al, 2022).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 97%